Prenatal Phthalate Exposures and Childhood Fat Mass in a New York City Cohort - Buckley, Jessie P. (Environ Health Perspect, 2015)
BACKGROUND: Experimental animal studies and limited epidemiologic evidence suggest that prenatal exposure to phthalates may be obesogenic, with potential sex-specific effects of phthalates having anti-androgenic activity. OBJECTIVES: We aimed to assess associations between prenatal phthalate exposures and childhood fat mass in a prospective cohort study. METHODS: We measured phthalate metabolite concentrations in third-trimester maternal urine in a cohort of women enrolled in New York City between 1998 and 2002 (n = 404). Among 180 children (82 girls and 98 boys), we evaluated body composition using a Tanita scale at multiple follow-up visits between ages 4 and 9 years (363 total visits). We estimated associations of standard deviation differences or tertiles of natural log phthalate metabolite concentrations with percent fat mass using linear mixed-effects regression models with random intercepts for repeated outcome measurements. We assessed associations in multiple metabolite models and adjusted for covariates including prepregnancy body mass index, gestational weight gain, maternal smoking during pregnancy, and breastfeeding. RESULTS: We did not observe associations between maternal urinary phthalate concentrations and percent body fat in models examining continuous exposures. Fat mass was 3.06% (95% CI: –5.99, –0.09%) lower among children in the highest tertile of maternal urinary concentrations of summed di(2-ethylhexyl) phthalate (ΣDEHP) metabolites than in children in the lowest tertile. Though estimates were imprecise, there was little evidence that associations between maternal urinary phthalate concentrations and percent fat mass were modified by child’s sex. CONCLUSIONS: Prenatal phthalate exposures were not associated with increased body fat among children 4–9 years of age, though high prenatal DEHP exposure may be associated with lower fat mass in childhood. CITATION: Buckley JP, Engel SM, Mendez MA, Richardson DB, Daniels JL, Calafat AM, Wolff MS, Herring AH. 2016. Prenatal phthalate exposures and childhood fat mass in a New York City cohort. Environ Health Perspect 124:507–513; http://dx.doi.org/10.1289/ehp.1509788